Белорусская «трасянка» и украинский «суржик»: oб основных различиях в степени влияния русского языка - Hentschel, Gerd (Przegląd Rusycystyczny, 2018)
The article presents a comparison of two post-Soviet mixed languages basing on Russian and other East Slavonic languages: Ukariniana (Surzhik) and Belarussian (Trasyanka). The author considers the role of Russian influence in the process of forming new hybrid language forms.